Integrating project-based learning and jigsaw to enhance teaching competence among pre-service non-formal educators for elementary learning contexts - Desika Putri Mardiani; Sjafi'atul Mardliyah; Wiwin Yulianingsih; Danang Prastyo; Vany Fitria; Achmad Jalaludin Rumi (EduStream: Jurnal Pendidikan Dasar, 2026)
The objective of this study is to examine the effectiveness of integrating project-based learning (PJBL) and the Jigsaw cooperative strategy in improving the teaching competence of pre-service educators. Employing a quantitative experimental design, the research involved 80 undergraduate students enrolled in a Non-Formal Education Program, divided into 2 categories: an experimental group with PJBL-Jigsaw integration and a control group (conventional learning). Teaching competencies were assessed using a questionnaire validated through expert judgment and reliability testing (Cronbach’s alpha > 0.80), covering lesson planning, classroom management, instructional strategies, reflection, and evaluation. Paired-sample and independent-sample t-tests were used to analyze the data, complemented by effect size analysis (Cohen’s d). The results indicate a statistically substantial improvement in teaching competence in both groups; however, the experimental group demonstrated substantially greater mean score gains (increase of 32 points) compared to the control group (increase of 13 points). The effect size of the integrated PJBL-Jigsaw intervention was categorized as very large (d > 0.8). These findings confirm that integrating PJBL and Jigsaw strategies produces a strong and meaningful impact on the development of pedagogical competence among prospective educators. The study contributes empirical evidence supporting innovative, collaborative learning design in educator preparation.